Carpio Silence on China move tantamount to 'Disloyalty to Republic' - Dizon, Nikko (Philippine Daily Inquirer, 2017)
Supreme Court Senior Associate Justice Antonio Carpio said that the Duterte administration's failure to file a diplomatic protest against China over presence of its ships in Philippine land territory is tantamount to "disloyalty to the republic".